Laparoscopic low anterior resection for rectal cancer associated with Leriche syndrome: a case report - Ryo Nakanishi; Atsuko Tsutsui; Hiroto Tanaka; Kohei Mishima; Chie Hagiwara; Takahiro Ozaki; Kazuharu Igarashi; Satoru Ishii; Nobuhiko Okamoto; Kenji Omura; Go Wakabayashi (Surgical Case Reports)
Abstract A 78-year-old male presented with a positive fecal occult blood test. Rectal cancer was detected during lower gastrointestinal endoscopy, and further investigations led to a diagnosis of cT1N0M0 cStage I (UICC classification, 8th edition). Preoperative contrast-enhanced computed tomography (CT) showed that the patient also had Leriche syndrome, which is associated with reduced blood flow to the rectum that may result in ischemic anastomosis during rectal cancer surgery with anastomotic reconstruction. The inferior epigastric arteries often function as collateral pathways to the lower limbs in patients with Leriche syndrome; therefore, care is needed to avoid vascular damage during trocar insertion when performing laparoscopic surgeries. We herein described a case of safe laparoscopic low anterior resection in a rectal cancer patient with Leriche syndrome using vascular architecture images obtained by preoperative CT angiography.